Almost periodic dynamics of a discrete Nicholson’s blowflies model involving a linear harvesting term - Alzabut, Jehad; Bolat, Yaşar; Abdeljawad, Thabet (Springer Science and Business Media LLC, 2012)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Nicholson's blowflies model; Algebra and Number Theory; Population dynamics (general); exponential stability; Applied Mathematics; Almost periodic solutions of difference equations; Stability theory for difference equations; almost periodic solution; harvesting term; Analysis